Small‐Volume Plasmonic Microwell Array with 3D Hierarchical Nanomaterials for Plasmon‐Enhanced Fluorescence Immunoassay. Issue 1 (9th October 2020) - Choi, Wook; Lee, Won-Chul; Mun, ChaeWon; Kim, Sunho; Ansah, Iris Baffour; Kim, Shin-Hyun; Kim, Dong-Ho; Jung, Ho Sang; Park, Sung-Gyu
Abstract : Developing a small‐volume bioassay using microliter‐scale biofluids is crucial for achieving a rapid, sensitive, and high‐throughput screening and medical diagnosis. Herein, a new plasmonic microwell array (PMA) containing 3D hierarchical nanomaterials for multiplexed bioassays is presented. The microwell array is formed by performing a sequential bottom‐up fabrication involving dispensing UV‐curable photopolymers and plasmonic Ag nanowires (NWs) on a flat substrate. The plasmonic Ag NWs are developed into a multilayer stack of Ag@Au core‐shell NWs having surfaces densely decorated with Au nanoparticles. This multi‐stacked hybrid plasmonic nanostructure provided 3D multiscale hotspots and large effective surfaces for molecular binding sites. Highly improved sensitivities are demonstrated for a plasmon‐enhanced fluorescence‐based immunoassay of cardiac troponin I (cTnI), a diagnostic biomarker for acute myocardial infarction, using a small volume of 5 μL. The limit of detection is determined to be 2.02 pg mL −1 for cTnI, representing a 30‐fold greater sensitivity than the clinical cut‐off value. Furthermore, 3D PMA chips exhibit a highly uniform fluorescence intensity with a coefficient of variation of 3.4%. The 3D PMA provides a sensitive and reliable detection in a high‐throughput manner for point‐of‐care bioanalysis. Abstract : A small‐volume microwell array integrated with 3D hierarchical plasmonic nanomaterials is developed for sensitive and reliable multiplexed bioassays involving plasmon‐enhanced fluorescence immunoassaying. The 3D multiple‐microwell array exhibits a highly sensitive and uniform fluorescence intensity for immunoassaying of cardiac troponin I with a limit of detection of 2.02 pg mL −1 and a coefficient of variation of 3.4%, respectively.